Bhagavadajjukam in Kūṭiyāṭṭam : the hermit and the harlot, the Sanskrit farce in performance - Paulose, K. G. (New Bharatiya Book Corp., 2000)
Study of Bhagavadajjuka, classical Sanskrit play; includes text.